Formações discursivas atravessadas e identidades em trânsito: uma análise discursiva de/sobre sujeitos transexuais. - Filgueiras, Arthur de Araújo (2019)
This research aims to analyze the movement of clashes between discursive formations in the transsexual subjects' telling about their gender identity. As specific objectives, we seek to investigate the discursive and ideological formations of the subjects analyzed in the research; To analyze the effects of meaning that echo in the saying about the social name of transsexual subjects, as well as about the clothing. It also seeks to investigate the production of meaning effects in the process of transition to transsexuality, via surgical procedures and also the production of meaning effects in the constitution of transsexual identity from the clashes between discursive formations in discursive materialities present in the reports of life stories. For such purposes, the research has as theoretical and methodological support the French Discourse Analysis founded by Michel Pêcheux from the concepts of discursive formation, subject-position, interdiscourse and discursive memory, besides the notion of subject of the unconscious developed by Jacques Lacan that has implications on the subject subjectivation process. As we deal with gender identity and sexuality, we also use theorists such as Berenice Bento, Judith Butler, Michel Foucault, and others who will segment the reports analysis. The research was developed from semi-structured interviews with four transsexual subjects, two male and two female, for further analysis. Once the subjects are chosen, the discursive materiality collected in recordings were analyzed in order to search for the effects of meanings that are constructed from interdiscursivity and discursive heterogeneity. From the analysis, we observed that the construction of gender identity of transsexual subjects occurs in the midst of their subjectivation through the action of ideology and the unconscious in a process of alterity. In it, there is a flow of clashes between discursive formations that mark their subject-position, in the midst of the production of meaning effects not desired by the binary dominant ideology. Thus, body, social name and discourse objects produce meaning effects in a discourse of resistance to prejudiced hegemonic discourses, denouncing attempts to silence the existence of identities that crack patterns of a cultural intelligibility of genres. In addition, our analyzes also present, as a conclusion effect, the understanding that the constitution of gender identity and sexual orientation of these subjects are formed from a continuous flow in the movement of clashes between discursive formations, in certain ideological formations, that they do not cease to produce effects of meaning amid the corresponding discursive materialities.